2018
DOI: 10.1590/1983-21252018v31n305rc
|View full text |Cite
|
Sign up to set email alerts
|

REACTION OF BANANA CULTIVARS TO THE Meloidogyne javanica X Fusarium oxysporum f. sp. cubense COMPLEX

Abstract: The interaction Fusarium oxysporum f. sp. cubense (Foc) x nematode and the genetic variability of Foc are the main problems with potential to affect the use of resistant varieties in the management of the Panama disease. The objective of this work was to evaluate the interaction between Foc and Meloidogyne javanica on the banana of the Prata Anã, Grande Naine and BRS Princesa cultivars. The experiment was conducted in a randomized block design, with six treatments and ten replications, which differed in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
5
0
4
Order By: Relevance
“…In addition to the variants that exist in the Foc population, the interaction of the fungal pathogens with nematodes may interfere with the expression and durability of resistance to FW. The breakdown of resistance is not only related to the damage caused by the nematodes that allow the pathogen to enter the roots, but also to the production and secretion of proteins associated with the pathogenicity that interfere with gene expression and the cell metabolism of the host plant (Davis et al 2000;Hussey et al 2002;Davis et al 2004;Rocha et al 2018). Previous studies assessed the effects of the interactions between Foc and R. similis in banana cultivars using susceptible and moderately susceptible cultivars to FW.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the variants that exist in the Foc population, the interaction of the fungal pathogens with nematodes may interfere with the expression and durability of resistance to FW. The breakdown of resistance is not only related to the damage caused by the nematodes that allow the pathogen to enter the roots, but also to the production and secretion of proteins associated with the pathogenicity that interfere with gene expression and the cell metabolism of the host plant (Davis et al 2000;Hussey et al 2002;Davis et al 2004;Rocha et al 2018). Previous studies assessed the effects of the interactions between Foc and R. similis in banana cultivars using susceptible and moderately susceptible cultivars to FW.…”
Section: Introductionmentioning
confidence: 99%
“…Then, 40 mL of sterilized distilled water were added to the Petri dishes and, with the aid of a brush, the conidia were disaggregated. The suspension was filtered in a sterilized gauze, and the concentration of spores was calibrated in a hemacytometer to 1×10 6 spores/mL (CARVALHO, et al, 2021;ROCHA, et al, 2018;SILVA, et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the interaction Fusarium -Meloidogyne, several studies already confirmed that the nematode makes the plants more prone to infection by the fungus (ROCHA, et al, 2018, GOMES, et al, 2011PEREIRA, 2008). There are still no consistent results showing the interaction between M. incognita and F. solani in passion fruit crops.…”
Section: Fs Fs+mimentioning
confidence: 99%
See 1 more Smart Citation
“…É a segunda fruta mais consumida do planeta (Handique et al, 2019), sendo a Índia o maior produtor, com 1/3 do total da produção mundial (Ghag & Ganapathi, 2019). O Brasil é o quinto maior produtor (Rocha et al, 2018), com uma produção em 2017 de 6,735 milhões de toneladas em uma área de 468,754 mil hectares (Instituto Brasileiro de Geografia e Estatística, 2019). Atualmente, a safra brasileira é baseada em cultivares do subgrupo Prata, com destaque para o clone Prata Anã (AAB), Gorutuba e Catarina (Rocha et al, 2018), sendo que no Acre as cultivares predominantes são Prata Comum, D'Angola (conhecida regionalmente como banana-comprida), Maçã e Pacovan, além das cultivares que foram recomendadas pela Embrapa Acre: Thap Maeo, Maravilha, Preciosa, Pacovan Ken e Japira (Sá et al, 2016).…”
Section: Introductionunclassified